1998
DOI: 10.1073/pnas.95.6.3168
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of granule cell precursors in the dentate gyrus of adult monkeys is diminished by stress

Abstract: Although granule cells continue to be added to the dentate gyrus of adult rats and tree shrews, this phenomenon has not been demonstrated in the dentate gyrus of adult primates. To determine whether neurons are produced in the dentate gyrus of adult primates, adult marmoset monkeys (Callithrix jacchus) were injected with BrdU and perfused 2 hr or 3 weeks later. BrdU is a thymidine analog that is incorporated into proliferating cells during S phase. A substantial number of cells in the dentate gyrus of adult mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
669
3
16

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,203 publications
(723 citation statements)
references
References 27 publications
23
669
3
16
Order By: Relevance
“…The hippocampi of depressed patients are significantly smaller than those of healthy individuals (Sheline, 2000). This reduced volume may be the result of decreased neurogenesis in depressed individuals, a possi-bility supported by the findings that hippocampal neurogenesis is reduced by stress (Gould et al, 1998) and increased by antidepressant treatment (Malberg et al, 2000). The parallel changes in BDNF levels and neurogenesis in response to stress and antidepressant treatment suggest a connection between BDNF and hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 81%
“…The hippocampi of depressed patients are significantly smaller than those of healthy individuals (Sheline, 2000). This reduced volume may be the result of decreased neurogenesis in depressed individuals, a possi-bility supported by the findings that hippocampal neurogenesis is reduced by stress (Gould et al, 1998) and increased by antidepressant treatment (Malberg et al, 2000). The parallel changes in BDNF levels and neurogenesis in response to stress and antidepressant treatment suggest a connection between BDNF and hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 81%
“…Gould and McEwen have reported that exposure of marmoset monkeys or tree shrews to intruder stress for only a short period of time (1 h) down-regulates the rate of neurogenesis in adult hippocampus see Gould et al (1998). Administration of adrenal-glucocorticoids also decreases neurogenesis in adult hippocampus see McEwen1999), indicating that activation of the HPA axis and release of glucocorticoids underlies the downregulation of neurogenesis in response to stress.…”
Section: Stress Decreases Adult Neurogenesismentioning
confidence: 99%
“…The emphasis on studies of hippocampus stems in part from the work of McEwen and colleagues demonstrating that stress can have profound effects on the morphology of hippocampal neurons (see McEwen 1999;Gould et al 1998). This includes a decrease in the dendritic arborization of CA3 pyramidal neurons and down-regulation of neurogenesis of granule cells in adult dentate gyrus.…”
Section: Regulation Of Adult Neurogenesismentioning
confidence: 99%
“…However, only recently has neurogenesis become accepted as a general phenomenon in the brains of birds [1] , rodents [2][3][4][5] , monkeys [6] , and humans [7] . Further studies demonstrated that neurogenesis persisted in the mammal forebrain throughout the whole life [8,9] , and was modulated by both physiological stimuli and pathophysiological conditions [10,11] .…”
Section: Introductionmentioning
confidence: 99%